The development of marketing mix strategies for natural tourism in Phetchabun province. - Lachai, Thamonwan (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aimed to: 1) study tourism behavior of tourists in Phetchabun Province; 2) study the level of marketing mix of natural tourism in Phetchabun Province; 3) compare the level of marketing mix of natural tourism in Phetchabun Province as classified by personal factors; and 4) study suggested guidelines for developing the marketing mix strategies for natural tourism in Phetchabun Province. This study was a mixed methods research consisting of quantitative research, where the data were collected from 400 tourists in Phetchabun province using a questionnaire, and then statistically analyzed, and qualitative research using in-depth interviews with key informants. The findings of this research were as follows: 1. In term of tourist behavior in Phetchabun province, most of the tourists were female aged 31-40 years, working as an employee in a private company with an average monthly income of 15,001 – 25,000 Baht and had the domicile place in Northeastern. The purpose of their traveling included visiting natural attractions. They traveled by their own car. Most of them had ever travelled for more than 2 times and they traveled with a group of friends on the public holiday. They spent 1 night with the travelling expenses of 1,001 – 5,000 Baht. The main activity of the tourist during travelling was mostly to take the photos. The souvenirs that tourists mostly bought were processed products such as processed tamarind or organic pickled mustard. The media that made the attractions became well-known was the word of mouth from relatives or friends. 2. The level of marketing mix of natural tourism in Phetchabun Province was overall at the moderate level. When each aspect was considered, product was in the highest level, followed by process, price, physical environment, place, personnel, and promotion, respectively. 3. The comparison of the level of marketing mix of natural tourism in Phetchabun Province categorized by personal factors revealed that different gender and domicile place of tourists had indifferent level of marketing mix of natural tourism in Phetchabun Province, while tourists with different age, career, and average monthly income had different level of marketing mix of natural tourism at the significant level of .05. 4. Suggested guidelines for developing marketing mix strategies for natural tourism in Phetchabun Province in each aspect were as follows. 1) Product: it should have facilities that are standardized, safe and modern to meet the needs of tourists. 2) Price: the price must be controlled to be not too high or should be set to several levels in order to be selected by the tourists. 3) Place: the distribution channel should be varied such as internet, website or call center to provide services to the tourists. 4) Promotion: tourism should be promoted to encourage tourists to travel. 5) Personnel: the personnel should be trained to develop personality and etiquette including skills to provide accurate information to tourists. 6) Process: the sufficient number of personnel who are knowledgeable about tourist attractions. 7) Physical Environment: the landscape should be improved to be beautiful and interesting focusing on convenience, safety for life and property of tourists including mapping or signage should be clearly provided at various service points clearly. Article history : Received 25 December 2018 Revised 6 January 2019 Accepted 9 January 2019 SIMILARITY INDEX = 0.00